THE NEXUS BETWEEN EMPLOYEE HAPPINESS AND COMPANY PERFORMANCE - Maria-Teodora PAPAINOG (Financial Studies)
This article examines the relationship between worker satisfaction and business profitability, particularly emphasizing the pandemic era. It offers a fresh viewpoint on how a person's happiness may be critical in developing a business. The empirical study focuses on approximately 12,343 companies operating in various sectors, for which financial data for the reference period 2013-2022 were collected from the ORBIS platform. Quantile regression and panel smooth transition regression models were used as estimation methodologies. The findings have shown that employee satisfaction generally has a detrimental impact on a company's profitability, with a significantly more evident effect on companies with very low ROA and ROE indicators. Furthermore, it has been demonstrated that, although the influence is less pronounced in absolute terms, the relationship between happiness and profitability within successful enterprises becomes increasingly positive. Additionally, the COVID-19 pandemic has brought about notable changes in the dynamics between these two variables, revealing that a rise in employee happiness during the pandemic contributed to increased profitability in companies with lower productivity. Conversely, it resulted in a decline in profitability for firms exhibiting exceptionally high ROA or ROE indicators.